Effect of petrochemical sludge concentrations on microbial communities during soil bioremediation - Del Panno, María Teresa (2005)
Qualitative and quantitative changes of microbial communities in soil microcosms during bioremediation were determined throughout one year. The soil was contaminated with 0%, 2.5%, 5%, 10% (wt/wt) of petrochemical sludge containing polynuclear aromatic hydrocarbons. We analyzed the hydrocarbon concentration in the microcosms, the number of cultivable bacteria using CFU and most probable number assays, the community structure using denaturing gradient gel electrophoresis, and the metabolic activity of soil using dehydrogenase activity and substrate-induced respiration assays. After one year of treatment, the chemical analysis suggested that the hydrocarbon elimination process was over. The biological analysis, however, showed that the contaminated microcosms suffered under long-term disturbance. The number of heterotrophic bacteria that increased after sludge addition (up to 108-109 cells ml-1) has not returned to the level of the control soil (2-6 × 107 cells ml-1). The community structure in the contaminated soils differed considerably from that in the control. The substrate-induced respiration of the contaminated soils was significantly lower (≈10-fold) and the dehydrogenase activity was significantly higher (20-40-fold) compared to the control. Changes in the community structure of soils depended on the amount of added sludge. The species, which were predominant in the sludge community, could not be detected in the contaminated soils.